Knowledge, Attitude and Practices of Dental Practitioners against Hepatitis B in District Faisalabad - Dr.Abid Rashid; Dr. Ume Habiba; Dr. Muhammad Asif; Dr. Naseem Akhtar; Dr. Sultan Ayaz; Dr. Saadia Khatoon (Aziz Fatimah Medical and Dental College, 2021)
Objective: To assess the knowledge, attitude and practices of dental practitioners against Hepatitis B in district Faisalabad. Methodology: This descriptive cross-sectional study was conducted from 1st August 2019 to 31st January 2020. Sixty four dental practitioners who are practicing in Allied hospital Faisalabad and DHQ hospital Faisalabad were recruited by using simple random sampling technique, included in this study. The data was collected through self-administered questionnaires. Results: Mean age ± SD of the respondents was 31.6±2.8 years. On account of assessing knowledge, 52 dentists strongly agreed for proper hand washing in the prevention of Hepatitis B. For using barriers like gloves, gown and masks, 56 of the respondents strongly agreed. For using puncture-resistant containers for sharp disposal, 25 of the respondents strongly agreed. For using protective eye wares 46 agreed. Fifty nine of the respondents strongly agreed for the proper sterilization of instruments in the prevention of Hepatitis B. On account of practices against Hepatitis B, 52 respondents were vaccinated against hepatitis B. Twelve were not vaccinated. Forty six out of 52 had completed the course of vaccination. Five out of 52 failed to recall the history of their vaccination but 6 did not completed the course. Conclusion: A good percentage of dental practitioners have been vaccinated against hepatitis B. However, there is a need to increase this percentage, so that maximum number of dentists that come in direct contact with the persons could be prevented against this fatal disease.